Crystal structure of the site-specific recombinase, XerD. - Subramanya, H S (1997)
The structure of the site-specific recombinase, XerD, that functions in circular chromosome separation, has been solved at 2.5 A resolution and reveals that the protein comprises two domains. The C-terminal domain contains two conserved sequence motifs that are located in similar positions in the structures of XerD, lambda and HP1 integrases. However, the extreme C-terminal regions of the three proteins, containing the active site tyrosine, are very different. In XerD, the arrangement of active site residues supports a cis cleavage mechanism. Biochemical evidence for DNA bending is encompassed in a model that accommodates extensive biochemical and genetic data, and in which the DNA is wrapped around an alpha-helix in a manner similar to that observed for CAP complexed with DNA.